(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
In this paper a complex semantic-grammatical analysis impersonal and infinitive sentences by modern Ukrainian language. Place impersonal and infinitive sentences in composite structures already defined. Semantic-syntactic organization impersonal and infinitive of sentences, lexical filling determined. Means of expressing semantic components, their relationships with members of the formal syntactic structure of sentences is established. Syntactic relations and semantic-syntactic relations in sentences highlighted. Syntactic synonymy structures traced.